Cities and the Meanings of Late Antiquity - Mark Humphries (Brill Research Perspectives in Ancient History, 2019)
The last half century has seen an explosion in the study of late antiquity, largely prompted by the influence of the works of Peter Brown. This new scholarship has characterised the period between the third and seventh centuries not as one of catastrophic collapse, but rather as one of dynamic and positive transformation. Where observers formerly had seen only a bleak picture of decline and fall, a new generation of scholars preferred to emphasise how the Roman Empire evolved into the new polities, societies, and cultures of the medieval West, Byzantium, and Islam. Yet research on the fortunes of cities in this period has provoked challenges to this increasingly accepted positive picture of late antiquity and has prompted historians to speak once more in terms that evoke Edward Gibbon’s History of the Decline and Fall of the Roman Empire. This study surveys the nature of the current debate, examining problems associated with the sources historians use to examine late-antique urbanism, as well as the discourses and methodological approaches they have constructed from them. It aims to set out the difficulties and opportunities presented by the study of cities in late antiquity, how understanding the processes affecting them has issued challenges to the scholarly orthodoxy on late antiquity, and how the evidence suggests that this transitional period witnessed real upheaval and dislocation alongside continuity and innovation in cities around the Mediterranean.